Impelementasi model discovery learning berbasis media educandy terhadap hasil belajar IPAS peserta didik kelas IV sekolah dasar - Tri Septiana Sari; Fadhilah Khairani; Deviyanti Pangestu; Frida Destini (Universitas Sebelas Maret, 2025)
The problem in this study is the low learning outcomes of students in IPAS subjects in grade 4 of SD Negeri 1 Nunggalrejo. This happens because of the use of learning models and media that are less innovative. The purpose of this study was to determine the effect of discovery learning model based on educandy media on learning outcomes. The research design used is a non-equivalent control group design that uses experimental classes and control classes with a population and a sample of 40 students. Data collection techniques using tests and nontests. Data were analyzed through simple regression tests. The results of the simple regression test show that the results of Fcount> Ftable are 77,353 > 4.41 with a significance of 0.000 <0.05, which means that there is a significant effect on the implementation of the discovery learning model based on educandy media on the learning outcomes of IPAS class IV elementary school students.